2021
DOI: 10.1038/s41591-020-01210-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tobacco control policies on global smoking prevalence

Abstract: Substantial global effort has been devoted to curtailing the tobacco epidemic over the past two decades, especially after the adoption of the Framework Convention on Tobacco Control1 by the World Health Organization in 2003. In 2015, in recognition of the burden resulting from tobacco use, strengthened tobacco control was included as a global development target in the 2030 Agenda for Sustainable Development2. Here we show that comprehensive tobacco control policies—including smoking bans, health warnings, adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 24 publications
5
98
1
1
Order By: Relevance
“…In fact, a ban on advertising should be used in the context of other measures. In other studies, our group estimated the health and cost effects of applying tax increase, plain packaging, and smoke-free strategies in the region and found that the first strategy had the most significant effect [ 22 , 25 , 44 , 45 ]. However, as it occurs with the other measures, the effects of a comprehensive ban on tobacco advertising and sponsorship would result in important health benefits and savings for the health systems in the region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a ban on advertising should be used in the context of other measures. In other studies, our group estimated the health and cost effects of applying tax increase, plain packaging, and smoke-free strategies in the region and found that the first strategy had the most significant effect [ 22 , 25 , 44 , 45 ]. However, as it occurs with the other measures, the effects of a comprehensive ban on tobacco advertising and sponsorship would result in important health benefits and savings for the health systems in the region.…”
Section: Discussionmentioning
confidence: 99%
“…These measures include: Monitoring tobacco use and tobacco control measures (Article 20); Protecting people from tobacco smoke (Article 8); Offering help to quit tobacco (Article 14); Warning people about the dangers of tobacco (Articles 11 and 12); Enforcing bans on tobacco advertising, promotion and sponsorship (Article 13); and Raising tobacco taxes (Article 6) [ 18 , 19 ]. Despite an accelerating impact of MPOWER policies, the implementation of legislation related to tobacco advertising at a global level is still limited [ 20 , 21 , 22 ]; moreover, scarcity of quality information at a country-level, lobbying, and constituency building from the tobacco industry have delayed the implementation and enforcement of these measures in Latin America [ 23 , 24 ]. In the group of studied countries, Peru and Bolivia have the minimum level of implementation; Argentina and Mexico are in an intermediate level of implementation with a ban of advertising on national television, radio, print media, and some direct or indirect forms of advertising, and although Colombia, Brazil, and Chile have the maximum level of implementation with a comprehensive ban of all forms of advertising, there is still room for improvement in the compliance of measures [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco was identified as a group 1 carcinogen that contributes to OSCC and currently remains one of the most dominant risk factors for OSCC. In 2017, cigarette smoking accounted for a large share in Asia, including Indonesia, China, and Mongolia [ 25 ]. Remarkably, due to the large population base, there were more OSCC patients in China than in other countries [ 24 ] and caused a heavier burden on the country.…”
Section: Overview On Oscc and Chemoresistancementioning
confidence: 99%
“…For instance, considering the deadly and addictive design of cigarettes, stronger policies such as taxes, advertising and sales bans are necessary to counteract the commercial push. Comprehensive advertising bans in various settings (schools, hospitals, restaurants) have been associated with significant reductions in smoking rates [ 19 ]. As part of the National Prevention Agreement in the Netherlands, the visible display of tobacco products in stores has not been allowed since 2020.…”
Section: ‘Hard’ Policiesmentioning
confidence: 99%